2018
DOI: 10.1186/s13256-018-1681-4
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus reactivation in a critically ill patient: a case report

Abstract: BackgroundThe aim of this case report is to discuss diagnostic workup and clinical management of cytomegalovirus reactivation in a critically ill immunocompetent pediatric patient.Case presentationA 2-year-old white boy who had no medical history presented with respiratory distress and fever. His Pediatric Risk of Mortality and Pediatric Logistic Organ Dysfunction scores were 20 and 11, respectively. Our preliminary diagnosis was multiple organ dysfunction secondary to sepsis. Antibiotic treatment was started;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Kogawa et al (2014) reported high serum levels of bilirubin and ferritin in EBVinfected children carriers of hemophagocytic lymphohistiocytosis, which worsened the prognosis of the disease [25]. Also, increased levels of serum ferritin were found in CMVinfected individuals and patients with acute mononucleosis [26][27][28][29]. In this study, high levels of serum ferritin were associated with EBV infection and EBV/CMV coinfection.…”
Section: Discussionsupporting
confidence: 52%
“…Kogawa et al (2014) reported high serum levels of bilirubin and ferritin in EBVinfected children carriers of hemophagocytic lymphohistiocytosis, which worsened the prognosis of the disease [25]. Also, increased levels of serum ferritin were found in CMVinfected individuals and patients with acute mononucleosis [26][27][28][29]. In this study, high levels of serum ferritin were associated with EBV infection and EBV/CMV coinfection.…”
Section: Discussionsupporting
confidence: 52%
“…Persistent NK cell dysfunction was closely related to sepsis induced immunosuppression, making patients more prone to secondary infection or latent virus reactivation and leading to poorerprognosis. 40,41 This also explained the sequential decrease in the absolute values of NK cells in the three groups.…”
Section: Discussionmentioning
confidence: 69%
“…Persistent NK cell dysfunction was closely related to sepsis induced immunosuppression, making patients more prone to secondary infection or latent virus reactivation and leading to poorerprognosis. 40,41 This also explained the sequential decrease in the absolute values of NK cells in the three groups.
Figure 4.Comparison of the proportion of peripheral blood lymphocyte subpopulation in each group. The data were averaged and tested by Mann–Whitney U test.
…”
Section: Discussionmentioning
confidence: 77%
“… 28 It has been found that reduced and dysfunctional NK cells are closely associated with sepsis-induced immunosuppression, leading to a greater susceptibility to infection and a poorer prognosis for patients. 29 , 30 It is evident that these intrinsic immune cells play an important role in the regulation of inflammation in sepsis. On the other hand, sepsis increases apoptosis, which may lead to a decrease in the number of CD4 T cells, 31 and significantly reduces the proliferative capacity of CD4 T cells.…”
Section: Discussionmentioning
confidence: 99%